Low temperature hydrothermal treatment of palm fiber fuel for simultaneous potassium removal, enhanced oil recovery and biogas production. (15th December 2018) - Tan, Chhenglong; Saritpongteeraka, Kanyarat; Kungsanant, Suratsawadee; Charnnok, Boonya; Chaiprapat, Sumate
Graphical abstract: Highlights: Hydrothermal treatment of EFB notably reduced slagging-fouling tendency in boiler. Optimized temp, holding time and biomass/liquid ratio achieved >90% K removal. Interrelationship of 3 key HTT variables was derived with quadratic regression. Additional oil recovery of 221.4 ton/yr can be attained with the proposed HTT scheme. Concentrate waste stream from HTT to anaerobic digester can increase methanation. Abstract: This work aims to solve the slagging and fouling problems in palm empty fruit bunch (EFB) power plant by means of simultaneous fuel quality improvement and enhanced recovery of EFB fiber oil and biogas from leaching liquid. Rapid accumulation of minerals on heat transfer surfaces has caused the EFB power plants frequent shutdowns for maintenance and considerable thermal efficiency loss. Hydrothermal treatment (HTT) of EFB was performed at low range temperatures (Temp) under various holding times (HT) and biomass-to-liquid ratios (B/L) aiming to improve fuel quality. Removal of potassium (K) was experimentally identified as the key indicator to reduce slagging and fouling indexes (SI and FI) of EFB ash. HTT at 120 °C, 120 min, and B/L 50 g/L gave best K removal at 90.7%, leaving only 0.19 wt% in the fuel, although lesser conditions were also effective. A statistically significant quadratic regression model of K removal was constructed to show the interrelationship among these independent variables. Moreover, it was found that oil recovery from EFB could be enhanced by HTT, gaining an estimate of 221.4 ton/yr of additional oil in a mid-size palm oil mill. The HTT leachate with high organic content is also a potential substrate for methane production in an existing anaerobic digester in the mill. At the end, a practical integration of HTT to palm oil mill with EFB power plant was proposed.